Atenção à saúde bucal de estrangeiros que residem nos países de fronteira com o município de Foz do Iguaçu, Paraná: demanda e impacto financeiro - Gomes, Sandra Palmeira Melo (2018)
The health-disease process in border regions assumes idiosyncrasies, and may point to weaknesses in health services in general and especially oral health services. Social inequalities are prominent in these regions, mainly because they are places where there are contradictions, be they social, cultural, legal or even political. The border region also points to an environment of flows and interactions that exceed geographical and territorial boundaries. Although the search of the populations of other countries for health services is a reality in the border municipalities, it is observed that there are few studies on oral health, regarding the Brazilian border range. The aim of the study was to analyze the demand of foreigners and Brazilian residents in countries bordering the city of Foz do Iguaçu-PR, for dentistry assistance in the Unified Health System of this municipality. It was a descriptive, documentary and quantitative approach. Data collection was carried out in May and June 2017, and had as its primary source 751 dental records of foreigners and Brazilian residents in neighboring countries served in the dentistry services of the Basic Health Unit of Jardim América and Dental Specialties Center in the period of 2010 to 2015. They were analyzed using simple descriptive statistics.The profile of the user was defined as the majority of females 64.85% predominantly young with age between 15-19 years, 12.12% being 98.67% Brazilian residents in Paraguay. Concerning occupation, 76.43% of the medical records did not present this information, while 4.12% were "housewife", followed by 2.79% students and 1.06% farmer. The "main complaint" does not appear in 74.97% of the medical records. However, 10.12% sought the service for consultations and/or treatments, motivated by "pain" 7.72% and "dental caries" 2.26%. The 51.93% restorative treatment was the most accomplished procedure in basic care. Endodontics was the most sought after specialty in the Dental Specialties Center, 47.77%, with the highest percentage of abandonment and pendency of 56.78%. The Ministry of Health transferred R$ 1,532,300.00 to the Center of Dental Specialties and 21,691 users were attended in the period of the survey, which corresponds to the per capita value of R $ 70.64 or an average of R$ 11.77 per capita /year. Of the 247 users referred from the Basic Health Unit of Jardim América for specialties, R$ 17,448.08 was spent, which corresponds to 1.14% of the total value of the federal contribution. Bureaucratic and/or geographical barriers were identified. Underreporting of data was one of the limiting factors of the research. It is suggested training and sensitization of professionals in relation to the work process and feeding and use of the database, as well as future studies that may add to this research, increasing knowledge about oral health care in the triple border. The results of this study may be useful for management and, in a larger context, contribute to oral health practices and policies.